2013
DOI: 10.3109/09593985.2013.838614
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of reliability and validity of the Swedish version of the Self-Efficacy for Exercise Scale for older people

Abstract: The aim was to test aspects of reliability and validity of a Swedish version of the Self-Efficacy for Exercise Scale (SEE-SV) for older people. Floor and ceiling effects, item-total correlation, internal consistency, test--retest reliability, content and construct validity were tested on 39 older people, mean age 72 years (SD 3.3). Content validity was also tested on five physical therapists. The results showed no floor and ceiling effects. The ICC for the total score was 0.79 (95% CI 0.61-0.89). The median we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
(55 reference statements)
3
16
0
Order By: Relevance
“…These were statements about ''how confident I am'': (1) ''that I can accomplish my physical activity and exercise goals that I set''; (2) ''that I can be physically active or exercise even when I am feeling depressed'' and (3) ''that I can be physically active or exercise even without the support of my family or friends''. In accordance with others, we found that the statement about feeling depressed showed a low correlation (Rydwik, Hovmöller, and Boström, 2014). This type of statement might be particularly affected by status from day to day and therefore not as stable over time.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These were statements about ''how confident I am'': (1) ''that I can accomplish my physical activity and exercise goals that I set''; (2) ''that I can be physically active or exercise even when I am feeling depressed'' and (3) ''that I can be physically active or exercise even without the support of my family or friends''. In accordance with others, we found that the statement about feeling depressed showed a low correlation (Rydwik, Hovmöller, and Boström, 2014). This type of statement might be particularly affected by status from day to day and therefore not as stable over time.…”
Section: Discussionsupporting
confidence: 88%
“…The reliability analysis of the items showed that the median of linear weighted kappa indicated a substantial correlation (0.62). This is similar to the recent evaluations of another measure of self-efficacy for exercise with a median weighted kappa of 0.63 (Rydwik, Hovmöller, and Boström, 2014). However, caution should be observed when comparing kappa between instruments because kappa is dependent on the number of categories; the fewer the categories the higher the coefficient (Landis and Koch, 1977).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…One such measure, the Self-Efficacy for Exercise scale (SEE), was developed and verified as a valid and reliable tool in older populations, 17 and further applied to African American and Latino older adults 18 in the United States. The SEE has also been translated into Chinese 19 and Swedish, 20 and these two translated versions were evaluated for the reliability and validity in samples of Taiwanese and Swedish population. We found no scale in Korean for self-efficacy for exercise for older adults available; thus, we deemed the SEE scale a suitable choice for measuring self-efficacy expectation because it is developed specifically for older adults and easily applicable to them, owing to its short length.…”
Section: Introductionmentioning
confidence: 99%